A qualitative theory guided analysis of stroke survivors' perceived barriers and facilitators to physical activity. (October 2014) - Nicholson, Sarah L.; Donaghy, Marie; Johnston, Marie; Sniehotta, Falko F.; van Wijck, Frederike; Johnston, Derek; Greig, Carolyn; McMurdo, Marion E. T.; Mead, Gillian
Abstract Purpose: After stroke, physical activity and physical fitness levels are low, impacting on health, activity and participation. It is unclear how best to support stroke survivors to increase physical activity. Little is known about the barriers and facilitators to physical activity after stroke. Thus, our aim was to explore stroke survivors' perceived barriers and facilitators to physical activity. Methods: Semi-structured interviews with 13 ambulatory stroke survivors exploring perceived barriers and facilitators to physical activity post stroke were conducted in participants' homes, audio-recorded and transcribed verbatim. The Theoretical Domains Framework (TDF) informed content analysis of the interview transcripts. Results: Data saturation was reached after interviews with 13 participants (median age of 76 years (inter-quartile range (IQR) = 69–83 years). The median time since stroke was 345 d (IQR = 316–366 d). The most commonly reported TDF domains were "beliefs about capabilities", "environmental context and resources" and "social influence". The most commonly reported perceived motivators were: social interaction, beliefs of benefits of exercise, high self-efficacy and the necessity of routine behaviours. The most commonly reported perceived barriers were: lack of professional support on discharge from hospital and follow-up, transport issues to structured classes/interventions, lack of control and negative affect. Conclusions: Stroke survivors perceive several different barriers and facilitators to physical activity. Stroke services need to address barriers to physical activity and to build on facilitators to promote physical activity after stroke. Implications for Rehabilitation Physical activity post stroke can improve physical fitness and function, yet physical activity remains low among stroke survivors. Understanding stroke survivors' perceived barriers and facilitators to physical activity is essential to develop targeted interventions to increase physical activity. Beliefs about capabilities, environmental context and resources and social influences were the mostly commonly report influences on stroke survivors' perceived barriers and facilitators to physical activity.